Biofeedback Intervention for Stress, Anxiety, and Depression among Graduate Students in Public Health Nursing - Paul Ratanasiripong; Orawan Kaewboonchoo; Nop Ratanasiripong; Suda Hanklang; Pornlert Chumchai (Nursing Research and Practice)
Globally, graduate students have been found to have high prevalence of mental health problems. With increasing severity of mental health problems on university campuses and limited resources for mental health treatment, alternative interventions are needed. This study investigated the use of biofeedback training to help reduce symptoms of stress, anxiety, and depression. A sample of 60 graduate students in public health nursing was randomly assigned to either the biofeedback intervention or the control group. Results indicated that biofeedback intervention was effective in significantly reducing the levels of stress, anxiety, and depression over the 4-week period, while the control group had increases in symptoms of anxiety and depression over the same timeframe. As future leaders in the public health nursing arena, the more psychologically healthy the graduate students in public health nursing are, the better the public health nursing professionals they will be as they go forth to serve the community after graduation.